Wisata Puncak Becici: Kepuasan, Loyalitas, Dan Intensi Rekomendasi Wisatawan - Isnanda Zainur Rohman (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2019)
This study aims to determine the effect of tourist satisfaction on tourist loyalty. Then, the impact of tourist loyalty on the intention of tourists to recommend others visit the tourist attractions. A total of 221 respondents filled out the questionnaire given by the researcher when they visited a tourist attraction, Puncak Becici Yogyakarta. This place is a new destination in Yogyakarta, so research is needed to make this place better. The hypotheses were tested by regression analyses. The results showed that tourist satisfaction has a positive effect on tourist loyalty. Then, tourist loyalty has a positive effect on the intention of tourist recommendations. The implication is that people managing tourist attractions need to maintain the level of tourist satisfaction so that tourists become loyal, and then they will have the intention to recommend others visit. Keyword: Puncak Becici, tourist satisfaction, tourist loyalty, and intention to recommend